Tuning the activity of iminosugars: novel N-alkylated deoxynojirimycin derivatives as strong BuChE inhibitors - Ana I. Ahuja-Casarín; Penélope Merino-Montiel; José Luis Vega-Baez; Sara Montiel-Smith; Miguel X. Fernandes; Irene Lagunes; Inés Maya; José M. Padrón; Óscar López; José G. Fernández-Bolaños (Taylor & Francis Group, 2021)
We have designed unprecedented cholinesterase inhibitors based on 1-deoxynojirimycin as potential anti-Alzheimer's agents. Compounds are comprised of three key structural motifs: the iminosugar, for interaction with cholinesterase catalytic anionic site (CAS); a hydrocarbon tether with variable lengths, and a fragment derived from 2-phenylethanol for promoting interactions with peripheral anionic site (PAS). Title compounds exhibited good selectivity towards BuChE, strongly depending on the substitution pattern and the length of the tether. The lead compounds were found to be strong mixed inhibitors of BuChE (IC50 = 1.8 and 1.9 µM). The presumptive binding mode of the lead compound was analysed using molecular docking simulations, revealing H-bond interactions with the catalytic subsite (His438) and CAS (Trp82 and Glu197) and van der Waals interactions with PAS (Thr284, Pro285, Asn289). They also lacked significant antiproliferative activity against tumour and non-tumour cells at 100 µM, making them promising new agents for tackling Alzheimer's disease through the cholinergic approach.